Evaluation of non-timber forest products used as medicinal plants from East Kalimantan (Indonesia) to inhibit ?-glucosidase and free radicals - RICO RAMADHAN; RAMADHAN TOSEPU; PREECHA PHUWAPRAISIRISAN; RUDIANTO AMIRTA; KIETTIPUM PHONTREE; YAZDANIYAR FAJRI HALIMI FIRDAUS; NURLITA ABDULGANI; MUHAMMAD ZAINUL MUTTAQIN; SAPARWADI SAPARWADI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ramadhan R, Tosepu R, Phuwapraisirisan P, Amirta R, Phontree K, Firdaus YFH, Abdulgani N, Muttaqin MZ, Saparwardi. 2022. Evaluation of non-timber forest products used as medicinal plants from East Kalimantan (Indonesia) to inhibit ?-glucosidase and free radicals. Biodiversitas 23: 5551-5558. Non-timber forest products (NTFPs) have essential uses as medicines, food sources, and traditional ceremonies for the local people living in forest areas. Medicinal plants are one of the non-timber forest products used as traditional medicine by local people in East Kalimantan. This study was conducted to search for new natural antidiabetic and antioxidant resources from medicinal plants used traditionally in Mahakam Ulu District, East Kalimantan, based on ethnopharmacological information. The present study evaluates non-timber forest products as in vitro antidiabetic (rat intestinal ?-glucosidase inhibitory activity) and antioxidant (free radical scavenging activity against DPPH, ABTS, and Nitric Oxide) activities. The antidiabetic and antioxidant activities were evaluated using ?-glucosidase inhibition assay and free radical scavenging methods. This study demonstrated that methanol extracts of Flacourtia rukam Zoll. & Moritzi, Syzygium chloranthum (Duthie) Merr. & L.M. Perry and Shorea balangeran Burck exhibited strong ?-glucosidase inhibitory activity with maltose as a substrate with IC50 values of 0.034 mg/mL, 0.039 mg/mL, and 0.039 mg/mL, respectively. On the other hand, methanol extract of S. chloranthum displayed the strongest ?-glucosidase inhibitory activity in sucrose as a substrate, similar to the IC50 value of the quercetin as a positive control. Furthermore, the antioxidant test showed that all medicinal plant extracts from East Kalimantan are good sources of natural antioxidants indicated by their IC50 values. The results of this study support the scientific background of the uses of medicinal plant extracts from East Kalimantan as folk medicine.